Characteristics and Outcomes of Acinetobacter baumannii Infections in Patients with HIV: A Matched Case-Control Study. Issue 1 (December 2018) - Yang, Junyang; Tang, Qi; Qi, Tangkai; Chen, Jun; Ji, Yongjia; Tang, Yang; Wang, Zhenyan; Song, Wei; Xun, Jingna; Liu, Li; Shen, Yinzhong; Zhang, Renfang; et al.
Abstract Acinetobacter baumannii (AB) infection is an increasing global threaten to hospitalized patients, especially those with impaired immune function. Still, few studies addressed the disease burdens and outcomes of AB infection in HIV patients. We aimed to describe characteristics and outcomes of AB infections in patients with HIV, measure the impact of AB infection on 28-day mortality in HIV patients, as well as assess the predictors of 28-day survival among HIV patients with AB pneumonia. A retrospective study with HIV/AB co-infected patients was conducted at Shanghai Public Health Clinical Center (SPHCC), China. Patients with AB pneumonia were further analyzed for predictors of mortality, as well as an additional 1:1 case-control study to determine the fatality of AB pneumonia compared with pneumonia of other pathogens. We found the incidence of AB infection was 17.4 cases per 100 person-years among all hospitalized HIV patients. Hospital mortality rate was 37.5% (21/56). There was a higher 28-day mortality rate in HIV patients with pneumonia due to AB than other pathogens (34% vs 16%, P = 0.03). APACHE II score was independently associated with 28-day survival by multivariate logistic regression (P = 0.031). Our findings indicate that AB infection is incident and can be fatal in HIV seropositive population. AB infection is an independent risk factor of mortality in patients with HIV and pneumonia. A lower APACHE II score on admission predicts a higher 28-day survival rate among HIV/AB co-infected patients.